Mineral resource base of Russia’s copper: current state and development prospects - Grigory Yu. Boyarko; Anna M. Lapteva; Liudmila M. Bolsunovskaya (Горные науки и технологии)
This study addresses the need for a comprehensive understanding of current state of Russia’s cupper mineral resource base. Its objective is to assess Russia’s copper reserves (balance reserves and forecast resources), analyze the spatial distribution of copper deposits by ore formation types and across ore provinces, and evaluate prospects for sustaining national copper production. Methods: The study employs statistical, graphical, and logical analysis methods. Results: The research presents a consolidated map of Russia, highlighting 25 copper provinces and 150 significant copper deposits across various ore formations, as well as prospective sites and areas. Key characteristics of Russia’s main ore formations, copper ore provinces, and outlying copper deposits are detailed. Copper production in Russia is currently concentrated in sulfide copper-nickel and copper-pyrite deposits, with emerging mining operations in copper-porphyry and copper-skarn formations. In 2021, copper production in Russia reached 1,147 Kt. Upcoming projects to develop copper deposits could increase annual production by 635–1,053 Kt, equivalent to a 55–91% rise over 2021 levels. The total estimated balance reserves and forecast resources amount to 102.7 million tons, with conditional reserves accounting for 16.1 million tons. The largest copper reserves are found in copper-nickel formations (34.4%), copper-porphyry formations (23.9%), copper sandstones formation (19.6%), and copper-pyrite formation (14.5%), with all other formations contributing 7.6%. Key provinces include Norilsk-Kharayelakh (30.9% Russian reserves), Kodar-Udokan (20.3%), and the Urals (18.9). The share of reserves is growing in newer provinces: Primorsky (8.29%), Okhotsk-Chukotka (6.23%), and East Tuvinian (3.7%). Remaining copper mining provinces account for 11.68% of reserves. Current reserves are estimated to suffice for at least 47 years of optimal extraction. The most substantial reserves are associated with copper-nickel, copper-porphyry, and copper sandstone formations, whereas balance ore reserves in copper-pyrite and copper-skarn formations are nearly exhausted. Sufficient reserve security is available in the Norilsk-Kharayelakh, Kola, and Rudny Altai provinces. However, sugnificant reserve is observed in the traditional Ural and emerging East Trans-Baikal provinces. In the North Caucasus province, a high security results in low production levels and underutilized reserve deposits. The copper-nickel formation’s reserve availability remains low, though new rich ore deposits may exist at greater depths within the Kharaelakh and Tangaralakh ore-bearing intrusions. Copper-pyrite formation reserves may expand with further exploration of deep horizons and the periphery of known deposits in the Ural province, alongside new deposits discoveries in the Circumpolar and Polar Urals. For copper-polymetallic formation, extensive deposits exist in old Ore-Altai, Salair, and North Caucasian provinces, with promising potential in the new East Tuvinian and Okhotsk-Chukotka provinces. Exploration for porphyry copper has intensified in the East Tuvinian, Primorsky, and Okhotsk-Chukotka provinces, indicating strong potential for discovering new large porphyry copper deposits. Additional reserves of copper sandstone formation may be developed within the Kodar-Udokanskaya, Igarskaya, Bilyakchan-Kolyma, and Shoria-Khakass provinces. New technology for underground copper leaching opens opportunities for exploring and utilizing smaller copper sandstone deposits in the Pre-Ural and Donetsk provinces. The recorded cooper balance reserves in Russia do not yet account for native copper deposits in basaltoid formations within the Shoria-Khakass, Norilsk-Kharayelakhskaya, and Bilyakchan-Kolyma provinces.